Verfahren zur Herstellung von Saucen - GERARD TUYNENBURG MUYS; JACOB ARIE SCHAAP (1970)
1,130,634. Food dressings. UNILEVER Ltd. 25 Jan., 1967 [27 Jan., 1966], No. 3665/66 Heading A2B. In the production of food dressings comprising an emulsion of an oily medium, an acidified aqueous medium, and a substantial quantity of egg yolk, the components are deoxygenated, preferably to an oxygen content of less than 0.1 p.p.m., and then the components are processed in the substantial absence of oxygen. The deoxygenation may be effected by bubbling an inert gas through the components, if desired with the addition of heating, stirring and the application of a vacuum, or, in the case of the yolk, by fermentation with for example Lactobacteriaceae, such as Streptococcus Sp., Leuconostoc Sp., or Lactobacillus Sp.